Inventario de los principales deslizamientos en la vía Piuntza Yacuambi, cantón Yacuambi provincia de Zamora Chinchipe. - Cabrera Armijos, Elister Jesús (2011)
he province of Zamora Chinchipe is located in the West of Ecuador Southern Region in the Andes, which is at risk of threats or geological risks that may be by steep slopes, sudden changes in temperature and heavy rainfall for this reason one of the most delicate and also fundamental in any territorial planning point is the confrontation between the characteristics of the natural environment and possible uses that society does or wants to do the same. Landslides occur mainly in areas that have been affected in their natural constitution, such as slopes in areas that have been modified by the construction of roads or paths. In the province of Zamora this is a very common problem because of its geographical location, which gives the conditions of instability and detonation of landslides. The Piuntza-Yacuambi route currently affected by these phenomena, and when this road one of the main means of progress populations Yacuambi and Zamora as well as the settlements that are in the way of it, is It is given the need for studies to minimize losses in all the damages that can cause landslides not being controlled. This sector in presenting varied climates, is subject to conditions change, both lithological and structural, which has determined that it is extremely vulnerable to geological phenomena, of which they most often are the landslides area. This study is a contribution to the knowledge of the major geological phenomena that occur in the course of the Piuntza-Yacuambi way as in the landslide inventory, the same which aims to obtain a database with the aim of proposing measures more chords to enable better management and control of these geological phenomena.